High spatial resolution images for the analysis of the spatial structure of Pinus pinaster Aiton stands in Madrid (Spain) - Merino de Miguel, S.; Solana Gutierrez, J.; Gonzalez Alonso, F. (Forest Systems, 2010)
This paper analyses the spatial structure of the Pinus pinaster Aiton stands within Madrid province (Central Spain) by means of high spatial resolution images, as well as the relationship between texture indexes obtained from variograms, and dasometric features of forest stands. In order to carry out this research, some orthophotographs and an IKONOS satellite image were used. All these images corresponded to locations of the Spanish National Forest Inventory (NFI) sample plots for the species of interest. Image analysis was based on geostatistic tools and particularly on the variogram. Experimental variograms were calculated using the different data sets. The following step consisted on fitting mathematical functions to them in order to produce ideal variograms. These models were used to extract a set of variogram variables that might be useful for characterizing forest stands at different spatial resolutions. As a result, some significant relationships between variogram parameters and dasometric variables were found, but of limited predictive power. The latter reveals the diff iculties in applying such methodology when working on complex topographies and spatially heterogeneous forests as the Mediterranean.